INVESTIGATION OF THE EFFECT OF STUDENT ACHIEVEMENT ON THE CASE STUDY METHOD IN SCIENCE AND TECHNOLOGY COURSE STATES OF MATTER AND HEAT SUBJECT - Cihat DEMİR (International Journal of Eurasia Social Sciences, 2017)
It seems like a difficult lesson for the students because of the reasons that the subjects of science are abstract, not related to everyday life and adhere to traditional methods. One of the contemporary methods used as an alternative to traditional methods is the case method. The purpose of this study is to investigate the effect of the case study method on the academic achievement of the students in terms of states of matter and heat of the 8th grade science and technology course. The study group consists of 40 students in the 8th grade of a public school in the province of Diyarbakır in the academic year 2016-2017. "States of matter and heat achievement test" was used as data collection tool. Pre-test and post-test experiment group models were used in the study. Experimental group students trained by the case study method on the states of matter and heat subject. States of matter and heat achievement test was applied as pre-test and post-test. In the analysis of the data, SPSS 21.0 package program was used. According to the results of the study; t test results showed that there was a significant difference (p <.05) between the final test and the pre-test. According to the results of the study, necessary suggestions were made to physics education researchers and related institutions.